2022
DOI: 10.1177/27527530221090179
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review: The Evolution of Provider Knowledge, Attitudes, Perceptions and Perceived Barriers to Caring for Patients with Sickle Cell Disease 1970–Now

Abstract: Approximately 100,000 Americans have sickle cell disease (SCD). In the USA, the majority of patients with SCD are of African descent. Due to persistent racial and ethnic disparities in healthcare in the USA, patients with SCD experience disproportionately more health inequities because of providers’ implicit biases regarding patient race. Lack of access to health insurance, lack of transportation to healthcare providers, and inadequate provider knowledge contribute to the morbidity and mortality of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Therefore, household SES (ie, parental education),30–33 can directly affect the frequency of healthcare usage, matching our analyses’ trends. Although, visiting ER/urgent care frequently is often necessary for individuals living with SCD due to the nature of the condition and irrespective of their SES,14 25 existing studies have indicated that patients are hesitant to visit the ER/urgent care due to previous negative healthcare experiences and stigmatisation14 15 34 because of providers’ implicit biases 35. We acknowledge that there were many conflicting observations within the NHIS data set (eg, both highly educated and less than high school educated mothers visited the emergency department less often).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, household SES (ie, parental education),30–33 can directly affect the frequency of healthcare usage, matching our analyses’ trends. Although, visiting ER/urgent care frequently is often necessary for individuals living with SCD due to the nature of the condition and irrespective of their SES,14 25 existing studies have indicated that patients are hesitant to visit the ER/urgent care due to previous negative healthcare experiences and stigmatisation14 15 34 because of providers’ implicit biases 35. We acknowledge that there were many conflicting observations within the NHIS data set (eg, both highly educated and less than high school educated mothers visited the emergency department less often).…”
Section: Discussionmentioning
confidence: 99%
“…SDoH including socioeconomic status can directly affect the timeliness and quality of the children’s healthcare, which is consistent with the trends observed from our analyses. Moreover, studies have documented that SCD patients are hesitant to visit the emergency room/urgent care due to previous negative health experiences and stigmatization [ 32 , 35 ] because of the providers’ implicit biases [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study that reviewed surveys taken by patients with SCD in pediatric clinics found that a barrier to health care for patients in this population was access to a knowledgeable provider [ 5 ]. The first 2 years following transition to adult care in the population with SCD are associated with increased health care use and death [ 4 ], theorized to be partly due to poor patient knowledge and skills [ 6 ]. Thus, providing youth with SCD with adequate skills and knowledge to manage their own health care is important.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has not been a content analysis of web-based health information regarding transition to adulthood for patients with SCD. We defined adolescents and young adults as those aged 16-24 years per prior studies investigating the transition period [ 6 , 13 ]. The aims of this study were (1) to evaluate the readability, quality, and content of patient-facing information on the transition to adulthood for patients with SCD available on the internet; (2) to investigate the impact of website source and internet quality certifications on readability, quality measures, and content; and (3) to assess whether readability, quality, and content have improved over the course of 3 years.…”
Section: Introductionmentioning
confidence: 99%